DARI PREFERENSI KE POTENSI: KRITIK TERHADAP GAYA BELAJAR VARK DAN TAWARAN MODEL MULTIMODAL-TOLERAN LEARNING DESIGN (MTLD) DALAM PENDIDIKAN AGAMA ISLAM - Sayuti (Fakultas Tarbiyah IAI Almuslim Aceh, 2025)
The VARK learning style model has long been used in education to identify students' learning preferences. However, various studies have shown that this model has theoretical and practical weaknesses, including fixed labeling, simplification of learning potential, and a lack of empirical evidence regarding its effectiveness in improving learning outcomes. This research is crucial for evaluating these criticisms from the perspective of Islamic education, which upholds the principles of fitrah (natural disposition), justice, and diversity in the learning process. This study employed a non-empirical, qualitative approach in the form of a critical literature review, analyzing learning style theories, previous research findings, and concepts from Islamic education and learning differentiation. The study resulted in an alternative model called Multimodal-Tolerant Learning Design (MTLD), which integrates three main principles: active multimodality, pedagogical tolerance, and fitrah-based learning. These findings emphasize the importance of inclusive, flexible learning design rooted in Islamic values. Consequently, teachers need to develop learning strategies that stimulate all learning modalities and encourage the holistic growth of students, rather than simply adapting to dominant preferences.